Clinical Outcomes and Patient Satisfaction with a New Diffractive-Refractive Trifocal Intraocular Lens – A 12 Month Prospective Study - Brar S (Dove Medical Press, 2021)
Sheetal Brar, Sri Ganesh, Nikhil RP, Roopashree CR Department of Phaco-Refractive Surgery, Nethradhama Super Speciality Eye Hospital, Jayanagar, Bengaluru, Karnataka, 560070, IndiaCorrespondence: Sheetal BrarDepartment of Phaco-Refractive Surgery, Nethradhama Super Speciality Eye Hospital, 256/14, Kanakapura Main Road, 7th Block, Jayanagar, Bengaluru, Karnataka, 560070, IndiaTel +91 9591002092Email brar_sheetal@yahoo.co.inPurpose: To evaluate the clinical outcomes and patient satisfaction after implantation of Optiflex Trio, a new trifocal intraocular lens (IOL) following cataract surgery.Methods: Patients undergoing phacoemulsification for age-related cataracts and who satisfy the eligibility criteria underwent bilateral implantation with Optiflex Trio trifocal IOL. At follow -up visits of 1, 3, 6, and 12 months, binocular uncorrected and corrected distance, intermediate and near visual acuity, reading performance, contrast sensitivity (CS) and patient satisfaction for dysphotopsia and spectacle independence were evaluated using questionnaires.Results: A total of 54 eyes from 27 patients with mean age of 66.30± 7.48 years were included in the study. At 12 months, 78% (n = 21) patients had binocular cumulative UDVA of 20/20 or better. Post-op SE refraction accuracy was within ± 0.50 D for 93% (n = 50) eyes, and refractive cylinder accuracy was within ≤ 0.50 D in 94% (n = 51) eyes. The mean binocular UNVA was 0.01± 0.05 LogMAR, and the mean UIVA at 60 and 80 cm was 0.07± 0.06 and 0.03± 0.05 LogMAR, respectively, at 12 months. Reading speeds at 40, 60 and 80 cm showed improvement overtime. No patient had complained of severe dysphotopsia, and none of the patients required glasses for any activity. No eye underwent YAG-laser capsulotomy for significant PCO at the end of mean follow-up.Conclusion: After 12 months, Optiflex Trio trifocal IOL provided a complete visual restoration with good visual quality outcomes in terms of uncorrected distance, intermediate and near visual acuity. The incidence of dysphotopsia was low, and spectacle independence was high, resulting in good patient satisfaction.Trial Registry: CTRI/2019/10/021647 (www.ctri.nic.in).Keywords: Optiflex, trifocal, IOL, spectacle independence, intraocular lens